Student Character Transformation Through P5: A Study in Elementary School - Andayani, Dewi; Nurmalia, Laily; Kurniawan, Bayu Aji; Cukarso, Sulthan Hadist Ismaiedh (Journal of Innovation and Research in Primary Education, 2025)
The Pancasila Student Profile Strengthening Project (P5) is a program implemented in schools with the aim of forming student character through project-based learning. This study aims to determine the effectiveness of P5 in forming environmentally conscious characters in elementary schools. This study uses a qualitative method, with a narrative research design involving principal, one teacher, four students and four parents in one of the schools located in Cibitung District, Bekasi Regency, West Java Province, which was selected using the opportunistic sampling technique. Data collection was carried out through interviews, observations, and documentation studies. Inductive and thematic data analysis was carried out to identify, ignite, and create themes expressed by assistance participants with NVivo 12. This study resulted in the implementation of the Pancasila Student Profile Strengthening Project (P5) in elementary schools successfully forming students' characters who care about the environment, are responsible, and creative in managing waste, supported by a waste exchange system for money. However, recommendations for further research are the need for strategies to overcome challenges such as difficulty sorting waste and student differences.